2015
DOI: 10.18632/oncotarget.4603
|View full text |Cite
|
Sign up to set email alerts
|

The IMiDs targets IKZF-1/3 and IRF4 as novel negative regulators of NK cell-activating ligands expression in multiple myeloma

Abstract: Immunomodulatory drugs (IMiDs) have potent anti-tumor activities in multiple myeloma (MM) and are able to enhance the cytotoxic function of natural killer (NK) cells, important effectors of the immune response against MM. Here, we show that these drugs can enhance the expression of the NKG2D and DNAM-1 activating receptor ligands MICA and PVR/CD155 in human MM cell lines and primary malignant plasma cells. Depletion of cereblon (CRBN) by shRNA interference strongly impaired upregulation of these ligands and, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 64 publications
4
89
0
Order By: Relevance
“…The importance of enhancer-mediated CDCA7L expression in MM demonstrates the potential of translating basic mechanistic insights of tumour initiation towards development of therapeutic strategies. Indeed, downregulation of IRF4 in MM has been shown to be central to potent antitumour activities by immunomodulatory drugs1819. Similarly, bromodomain inhibition of the transcriptional co-activators CBP/EP300 is seen as a therapeutic strategy to target the IRF4 network in MM20.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of enhancer-mediated CDCA7L expression in MM demonstrates the potential of translating basic mechanistic insights of tumour initiation towards development of therapeutic strategies. Indeed, downregulation of IRF4 in MM has been shown to be central to potent antitumour activities by immunomodulatory drugs1819. Similarly, bromodomain inhibition of the transcriptional co-activators CBP/EP300 is seen as a therapeutic strategy to target the IRF4 network in MM20.…”
Section: Discussionmentioning
confidence: 99%
“…8 This notion has spurred great interest in developing strategies aimed at stimulating NK cell-mediated functions for MM immunotherapy. [9][10][11][12] The ability of anticancer chemotherapy and radiotherapy to enhance the immunogenic potential of malignant cells mainly relies on the establishment of immunogenic cell death (ICD) and release of DAMPs, including heat shock proteins (HSPs), high-mobility group box 1 proteins (HMGB1), ATP and the endoplasmic reticulum (ER) chaperone calreticulin. 13,14 In this context, both HSP70 and HMGB1 appear to exert an immunostimulatory activity by promoting DC maturation through TLR4, which, in turn, leads to the induction of antigen-specific T cell-mediated antitumor immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, our group has demonstrated that genotoxic drugs including doxorubicin and melphalan by generating reactive oxygen species (ROS) induce a DNA Damage Response (DDR)-dependent increase of activating NK receptor ligand expression on senescent tumor cells ( 14 ). More recently, we have also proven that expression of the NKG2D and DNAM-1 activating ligands MICA and PVR, is enhanced by immunomodulatory drugs (IMiDs) ( 24 ). It is well known that microtubules influence a variety of cell stress responses and act as coordinators of cell functions in response to stress ( 25 ).…”
Section: Introductionmentioning
confidence: 99%